Classification and Types of Geocentric Orbits - Richards, Yu, author 648384 (Delhi, India : University Publication : World Technologies, 2012)
A geocentric orbit involves any object orbiting the Earth, such as the Moon or artificial satellites. Currently there are approximately 2,465 artificial satellites orbiting the Earth and 6,216 pieces of space debris as tracked by the Goddard Space Flight Center. Over 16,291 previously launched objects have decayed into the Earth's atmosphere. Analemma a term in astronomy used to describe the plot of the positions of the Sun on the celestial sphere throughout one year. Closely resembles a figure-eight. Altitude as used here, the height of an object above the average surface of the Earth's oceans. Apogee is the farthest point that a satellite or celestial body can go from Earth, at which the orbital velocity will be at its minimum. Eccentricity a measure of how much an orbit deviates from a perfect circle. Eccentricity is strictly defined for all circular and elliptical orbits, and parabolic and hyperbolic trajectories. Equatorial plane as used here, an imaginary plane extending from the equator on the Earth to the celestial sphere Orbital characteristics the six parameters of the Keplerian elements needed to specify that orbit uniquely. Escape velocity as used here, the minimum velocity an object without propulsion needs to have to move away indefinitely from the Earth. An object at this velocity will enter a parabolic trajectory; above this velocity it will enter a hyperbolic trajectory. Impulse the integral of a force over the time during which it acts. Measured in (N-sec or Ib sec).